The Concept of Price and Service Quality at PT. Lion Super Indo, Palembang City, Islamic Economic Perspective - Agustina, Dian Nita; Allientia, Desti; Kumala Dewi, Intan; Salsabila, Syakira; Krisdayanti, Helisia (Universitas Pelita Harapan, 2025)
This research aims to analyze how the concepts of price and service quality are applied at PT. Lion Super Indo supermarket in Palembang City from an Islamic economic perspective. Through a qualitative approach that includes literature studies, field observations, and interviews with consumers, this study found that the strategies implemented by Super Indo are often perceived as unfair by consumers, particularly concerning non-transparent discounts. On the other hand, the quality of service is rated as quite good, although not fully consistent in terms of friendliness, cleanliness, and information delivery. The analysis results show that the application of Islamic economic values such as justice, transparency, trustworthiness, and honesty needs to be strengthened so that businesses do not solely focus on profit but also reflect Islamic ethics. This research contributes to guiding modern business practices to be more ethical and in line with Sharia principles.